The Man Who Never Died: The Life, Times, and Legacy of Joe Hill, American Labor Icon - Wallace, Len (Labour / Le Travail, 2013)
The article reviews the book, "The Man Who Never Died: The Life, Times, and Legacy of Joe Hill, American Labor Icon," by William M. Adler.
Keywords: ADLER, William M.; HILL, Joe, 1879-1915; MAN Who Never Died: The Life, Times & Legacy of Joe Hill, American Labor Icon, The (Book); Nonfiction